طبيعة العلاقة بين المعروض النقدي والقاعدة النقدية وسرعة دوران النقود في ليبيا خلال الفترة 2000-2020 - ابو عبودة, آمال (Sharwes Scientific Journal, 2025)
The study aims to clarify the relationship between the money supply, the monetary base, and the speed of money circulation in the Libyan economy and their impact on economic growth in Libya during the period 2000-2020 by analyzing the money supply and its components and identifying the important role that the money supply plays through analyzing some economic indicators. The descriptive analytical approach was relied upon by presenting The theoretical framework for the velocity of the money supply, focusing on the circulation of money, and addressing its concept, methods of measuring it, and the economic theories that explain it. The study also relied on the standard method using the ordinary least squares method through the statistical program (Eviews9 The study aims to clarify the importance of the money supply in influencing economic growth in Libya during the period 2000-2020 by analyzing the money supply and its components and identifying the important role that the money supply plays by analyzing some economic indicators. The descriptive analytical approach was relied upon by presenting The theoretical framework for the velocity of the money supply, focusing on the circulation of money, and addressing its concept, methods of measuring it, and the economic theories that explain it. The study also relied on the standard method using the ordinary least squares method through the statistical program (Eviews9), estimating the general trend equation between the time element (T) as an independent variable, and each of the dependent variables, which are the money supply, the monetary base, and the speed of money circulation. The study concluded with the most important results that showed the existence of a long-term relationship between the time factor as a dependent variable for all the functions used for the variables adopted in the study.